2006
DOI: 10.1097/01.ogx.0000216525.26292.36
|View full text |Cite
|
Sign up to set email alerts
|

Subcutaneous Depot Medroxyprogesterone Acetate versus Leuprolide Acetate in the Treatment of Endometriosis-Associated Pain

Abstract: BACKGROUND: A clinical study compared efficacy and safety of depot medroxyprogesterone acetate (DMPA) with leuprolide for endometriosis-associated pain. METHODS: This multicentre, 18 month, evaluator-blinded, comparatorcontrolled trial randomized 300 women with laparoscopically diagnosed endometriosis to 6 month treatment with subcutaneous injection of 104 mg/0.65 ml DMPA (DMPA-SC 104) every 3 months or leuprolide (3.75 mg monthly or 11.25 mg every 3 months), with 12 months post-treatment follow-up. Endpoints … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
61
0
4

Year Published

2011
2011
2018
2018

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 33 publications
(65 citation statements)
references
References 40 publications
0
61
0
4
Order By: Relevance
“…Limitations of GnRH-agonist therapy include the high recurrence rate (50% of patients show a relapse of symptoms within 6 months after therapy discontinuation) and side effects associated with the transitory pharmacologic menopause condition created: bone density loss, worsening of serum lipoprotein cholesterol distribution, depression, hot flashes, genitourinary atrophy, and decreased libido (135)(136)(137)(138)141). In adolescents treated with GnRH agonists, bone mineral density must be monitored with special care (140).…”
Section: Sex Steroids Expression Modulatorsmentioning
confidence: 99%
See 2 more Smart Citations
“…Limitations of GnRH-agonist therapy include the high recurrence rate (50% of patients show a relapse of symptoms within 6 months after therapy discontinuation) and side effects associated with the transitory pharmacologic menopause condition created: bone density loss, worsening of serum lipoprotein cholesterol distribution, depression, hot flashes, genitourinary atrophy, and decreased libido (135)(136)(137)(138)141). In adolescents treated with GnRH agonists, bone mineral density must be monitored with special care (140).…”
Section: Sex Steroids Expression Modulatorsmentioning
confidence: 99%
“…Oral contraceptives inhibit gonadal estrogen production through negative hypophyseal feedback (135)(136)(137). By suppressing ovarian activity, they may also reduce prostaglandin production secondary to endogenous estrogens and therefore decrease the inflammatory status (137).…”
Section: Sex Steroids Expression Modulatorsmentioning
confidence: 99%
See 1 more Smart Citation
“…By causing constant stimulation of GnRH receptors, leuprolide initially causes stimulation, but thereafter decreases, by receptor downregulation, pituitary secretion of LH and FSH. Like other GnRH agonists, leuprolide may be used in the treatment of hormone-responsive cancers such as prostate cancer or breast cancer as well as estrogen-dependent benign disorders like endometriosis [13] or uterine fibroids, to treat precocious puberty [14] and to control ovarian stimulation in in vitro fertilization. (Figure 7.5) is a synthetic decapeptide that blocks the effects of GnRH (GnRH antagonist).…”
Section: 26mentioning
confidence: 99%
“…In 2003, it was found that tetra-branched forms of neurotensin and its short functional fragment neurotensin (8)(9)(10)(11)(12)(13) are stable for 24 h in human plasma and serum, and their receptor affinity is even higher than that of the corresponding monomeric peptides. The protease-resistant oligo-branched form of neurotensin appeared as a promising alternative to stabilized neurotensin monomeric sequences [55,56] for tumor targeting).…”
Section: Branched Peptides As Tumor-targeting Agentsmentioning
confidence: 99%